The European company law action plan revisited : reassessment of the 2003 priorities of the European Commission - Geens, K. (Koen); Hopt, Klaus J., 1940- (Leuven : Leuven University Press, 2010)
The harmonisation of company law has always been on the agenda of the European Union. Besides the protection of third parties affected by business transactions, the founders had two other objectives: first, promoting freedom of establishment, and second, preventing the abuse of such freedom. In fact, the fear of the Netherlands becoming the 'Delaware of Europe'' (in terms of competition among Member States) seemed real, until, ironically, at the beginning of the 21st century, it was the privilege of the Dutch (and the Danish) state to fail in making the abuse argument before the European Court.
6. Monitoring by an Independent Board of Directors7. Monitoring by the Legislator; 8. What Should Be on the European Agenda?; Bibliography; Transcripts of Corporate Governance Session; A. Abstract; B. Response to paper by Eddy Wymeersch; C. Discussion; Paul DAVIES; Peter MONTAGNON, Association of British Insurers; Walter VAN GERVEN, K.U. Leuven; Jaap WINTER, University of Amsterdam; Bruno LAFORCE, GIMV NV; Philippe PELLE, European Commission; Klaus J. HOPT, Max Planck Institute; José GARRIDO GARCIA, University of Castilla-La Mancha; Didier MARTIN, Bredin Prat, Paris; Paul DAVIES; Hilde LAGA.
Includes bibliographical references.
Print version record.
English.
eBooks on EBSCOhost
Keywords: Corporation law -- European Union countries; Corporate governance -- European Union countries; Law -- European Union countries -- International unification; Law -- European Economic Community countries -- International unification; Gouvernement d'entreprise -- Pays de l'Union européenne.; Droit -- Pays de l'Union européenne -- Unification internationale; LAW -- International; LAW -- Corporate; Corporate governance; Corporation law; Law -- International unification; European Union countries